Effects of particle collection in a premixed stagnation flame synthesis of sub-stoichiometric TiO2-x nanoparticles. (16th January 2023) - Manuputty, Manoel Yohanes; Xu, Rong; Kraft, Markus
Graphical abstract: Highlights: Continuous collection method is introduced for stagnation flame synthesis. Continuous and interval collection methods are evaluated systematically. Oxygen vacancies and crystallinity are used to assess the collection effects. Continuous method allows for a longer operation while preserving particle properties. Abstract: Flame synthesis is a simple method to prepare sub-stoichiometric titanium dioxide ( TiO 2 - x ) nanoparticles. A rotating stagnation plate is often used as a substrate and to provide a cooling mechanism. The collection of particles from the rotating plate could be done in two ways: the conventional interval particle collection (IPC) method and a continuous particle collection (CPC). The effects of the deposition time and the rotation speed on the properties of titanium dioxide (TiO2 ) particles are investigated experimentally. For IPC, it was found that the properties of the collected samples are dependent on the deposition time. This creates an undesirable correlation between properties and synthesis yield. On the other hand, CPC approach allows for a continuous synthesis in which the particle properties are invariant with respect to the synthesis yield. The tunability of the particle properties is still achievable by controlling the rotation speed in the CPC.